2021
DOI: 10.2117/psysoc.2019-a108
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Bullying Victimization on Students’ Learning Weariness

Abstract: In China, learning weariness is the focus of attention, but few studies have explored the potential impact of bullying victimization on learning weariness. This study examines their relationship by exploring the mediating effect of two collectivism factors, attitude toward school and social alienation. One thousand one hundred and thirty-two students from 9 middle schools in rural China (11-15 years, 51.4% boys) participated in this study. Results show that bullying victimization has a significant impact on Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…On the one hand, peer victimization appears to be associated with alienation (e.g., Balan et al, 2018; Fabris et al, 2021). For instance, a correlational study documented that bullying victimization was significantly associated with social alienation among Chinese adolescents (Cui et al, 2021). Furthermore, a group difference study found that students reporting peer victimization showed high levels of social alienation (Delfabbro et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, peer victimization appears to be associated with alienation (e.g., Balan et al, 2018; Fabris et al, 2021). For instance, a correlational study documented that bullying victimization was significantly associated with social alienation among Chinese adolescents (Cui et al, 2021). Furthermore, a group difference study found that students reporting peer victimization showed high levels of social alienation (Delfabbro et al, 2006).…”
Section: Introductionmentioning
confidence: 99%